STRATEGI KOMUNIKASI KETUA KARANG TARUNA DALAM MENCEGAH NARKOBA DI KELURAHAN NUNANG DAYA BANGUN, KECAMATAN PAYAKUMBUH BARAT PAYAKUMBUH - Berliana Fitriani (Jurnal Komunikasi, 2024)
Communication strategies are of course very necessary in holding an activity. One of them is drug prevention carried out in an area. The high rate of drug abuse in Payakumbuh has made the Payakumbuh City BNN look for ways to overcome it, one of which is through youth organizations. The manifestation of this performance is faced with the communication strategy of the youth leadership to prevent drug trafficking. The purpose of this article is to look at the communication strategies used by youth leaders to prevent drugs in the Nunang Daya Bangun Village area, West Payakumbuh District, Payakumbuh. The methodology used is a descriptive qualitative type that will describe or explain research variables with data obtained from various sources. The communication strategy used by the chairman of the youth organization can be in the form of analysis and research of the situation, formulation of steps to be taken, program planning and implementation, feedback and evaluation. This communication strategy was said to be successful because the community became concerned about safe conditions and was active in warning and inviting the community to continue to protect their area from drug abuse